PERAN PENDIDIKAN NILAI PANCASILA DALAM MENCEGAH CYBERBULLYING PADA SISWA KELAS TINGGI SEKOLAH DASAR - Hutagalung, Rasmi Ariani; Salsabila, Nesya Zahra; Hia, Fini Artatina; Rahmadani, Nayla; sihombing, Delon Erlangga; Yunita, Sri (Universitas Negeri Medan, 2025)
This article aims to examine the instillation of Pancasila values as a preventive strategy in preventing cyberbullying behavior among adolescents. The prevalence of cyberbullying cases in the digital age indicates a crisis of character and a weak understanding of communication ethics in cyberspace. This study uses a descriptive qualitative method with a literature study approach, through analysis of various sources of books, scientific articles, and relevant previous research results. The results show that Pancasila values, particularly the values of humanity, unity, and social justice, are highly relevant in shaping the moral awareness, ethics, and empathy of adolescents in digital interactions. The instillation of these values is effectively carried out through an integrated approach between character education in schools, the active role of families, and the development of a supportive social environment. Thus, the internalization of Pancasila values not only strengthens the national identity of adolescents but also acts as a moral fortress in facing digital challenges.